GENDER JUSTICE TODAY - Chackalackal, Saju (Journal of Dharma, 2004)
Justice is a catchword insofar as we are at the receiving end, forming part of the group to which justice is being denied or whose rights are being violated. The normal dynamics of the justice machinery imply that those who deny justice would also be capable of withholding its reinstatement indefinitely, as many a time those violators sit at the helm of power centres. A counteraction, therefore, is possible only when the violated individuals (sometimes, along with a few from among the group identified as the violators themselves, they being not actively involved in such violations), after having realized the extent of what is being denied to them, could involve in a concerted effort to pave the way for the realization of justice, but always at a cost. This is true of every sphere where justice is challenged or denied, especially in the case of gender-related issues of justice-denial.